Craniosynostosis of the Lambdoid Suture - Rhodes, Jennifer L. (Thieme Medical Publishers, 2014)
Craniosynostosis affecting the lambdoid suture is uncommon. The definition of lambdoid craniosynostosis solely applies to those cases demonstrating true suture obliteration, similar to other forms of craniosynostosis. In patients presenting with posterior plagiocephaly, true lambdoid craniosynostosis must be differentiated from the much more common positional molding. It can occur in a unilateral form, a bilateral form, or as part of a complex craniosynostosis. In children with craniofacial syndromes, synostosis of the lambdoid suture most often is seen within the context of a pansynostotic picture. Chiari malformations are commonly seen in multisutural and syndromic types of craniosynostosis that affect the lambdoid sutures. Posterior cranial vault remodeling is recommended to provide adequate intracranial volume to allow for brain growth and to normalize the skull shape. Although many techniques have been described for the correction of lambdoid synostosis, optimal outcomes may result from those techniques based on the concept of occipital advancement.